2003
DOI: 10.4049/jimmunol.170.8.4036
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Fibrinogen-Like Protein 2/Fibroleukin Exhibits Immunosuppressive Properties: Suppressing T Cell Proliferation and Inhibiting Maturation of Bone Marrow-Derived Dendritic Cells

Abstract: Fibrinogen-like protein 2 (fgl2)/fibroleukin is a member of the fibrinogen-related protein superfamily. In addition to its established role in triggering thrombosis, it is known to be secreted by T cells. The soluble fgl2 (sfgl2) protein generated in a baculovirus expression system bound to both T cells and bone marrow-derived dendritic cells (DC) in a specific manner. sfgl2 exhibited immunomodulatory properties capable of inhibiting T cell proliferation stimulated by alloantigens, anti-CD3/anti-CD28 mAbs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
165
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(175 citation statements)
references
References 38 publications
7
165
1
2
Order By: Relevance
“…Accordingly, some of the effects mediated by alteration of fgl2 expression might reflect not simply altered thrombin deposition, but also an altered immune activation. As but one example, Chan et al (23) reported that fgl2 modified expression of costimulatory molecules on developing dendritic cells, with a profound "downstream" effect on cytokine induction following allostimulation. Current studies from our laboratory support the hypothesis that an additional immunomodulatory role for fgl2 does indeed follow binding to a receptor expressed in multiple tissues (R. Liu, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, some of the effects mediated by alteration of fgl2 expression might reflect not simply altered thrombin deposition, but also an altered immune activation. As but one example, Chan et al (23) reported that fgl2 modified expression of costimulatory molecules on developing dendritic cells, with a profound "downstream" effect on cytokine induction following allostimulation. Current studies from our laboratory support the hypothesis that an additional immunomodulatory role for fgl2 does indeed follow binding to a receptor expressed in multiple tissues (R. Liu, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…26 Previously we reported that in addition to its role in innate immunity as a membraneassociated prothrombinase, FGL2 also may have an important role in adaptive immune responses, similar to other members of the fibrinogen-like family of proteins, which include tenascin and angiopoietin. 27 Recombinant FGL2 was shown previously to suppress T cell proliferation to alloantigens, anti-CD3/CD28 antibodies, and Con A. 27 FGL2 also has been shown to inhibit maturation of bone marrow-derived dendritic cells (DCs) and polarized an allogeneic immune response toward a Th2 cytokine profile.…”
Section: Discussionmentioning
confidence: 99%
“…27 Recombinant FGL2 was shown previously to suppress T cell proliferation to alloantigens, anti-CD3/CD28 antibodies, and Con A. 27 FGL2 also has been shown to inhibit maturation of bone marrow-derived dendritic cells (DCs) and polarized an allogeneic immune response toward a Th2 cytokine profile. 27 In fgl2-deficient mice, Th1 cytokine levels and activity of DC, B, and T cells were all increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3c). This analysis suggested several such mechanisms, including suppressive soluble factors [12][13][14] , generation of extracellular adenosine [15][16][17][18] , and release of reactive oxygen 19 , and a possible, previously unanticipated role for T R cells in regulating wound repair.…”
mentioning
confidence: 99%